Unions' Collective Bargaining Agenda on Women's Issues: The Ontario Experience - Kumar, Pradeep; Acri, Lynn (Relations industrielles / Industrial Relations, 1992)
This paper examines the bargaining agenda of major Canadian unions in Ontario with respect to women's issues, and evaluates their efforts towards incorporating specific clauses pertaining to these issues into their collective agreements. The study reveals that union efforts to achieve a better deal for women have had mixed success.